Removal of doravirine by haemodialysis in people living with HIV with end-stage renal disease. (15th April 2022) - Moltó, José; Graterol, Fredzzia; Curran, Adrian; Ramos, Natalia; Imaz, Arkaitz; Sandoval, Diego; Pérez, Francisco; Bailón, Lucía; Khoo, Saye; Else, Laura; Paredes, Roger
Abstract: Objectives: To evaluate the effect of haemodialysis on doravirine concentrations in people living with HIV (PLWH) undergoing routine haemodialysis. Methods: An exploratory clinical trial that included PLWH undergoing intermittent haemodialysis was undertaken. After enrolment (day 1), doravirine 100 mg once daily was added to stable combined ART for 5 days. On day 6, blood samples were collected from each participant at the beginning and at the end of a dialysis session. Additionally, paired samples of blood entering ('in') and leaving ('out') the dialyser and the resulting dialysate were collected during the dialysis session to evaluate drug removal during dialysis. Doravirine concentrations in plasma and in the dialysate were determined by LC-MS/MS. The ratio of doravirine concentrations in plasma after/before the haemodialysis session and the haemodialysis extraction coefficient were calculated for each participant. The study was registered at https://www.clinicaltrials.gov (NCT04689737). Results: Eight participants (six male) were included. The median (range) age and BMI were 49.5 (28–67) years and 23.6 (17.9–34.2) kg/m 2, respectively. The doravirine dialysis extraction ratio was 34.3% (25.8%–41.4%). The ratio of doravirine concentrations in plasma after/before the haemodialysis session was 0.8 (0.6–1.0). At the end of the haemodialysis session (time post-dose 20.8–27.3 h), doravirine concentrations in plasma were 785 (101–1851) ng/mL. Conclusions: Despite moderate removal of doravirine by haemodialysis, trough doravirine concentrations in plasma after the haemodialysis sessions remained in excess of the protein-binding-adjusted EC50 (5 ng/mL). Doravirine dosage adjustments are unnecessary in PLWH undergoing intermittent haemodialysis.